2020
DOI: 10.4018/ijmbl.2020010102
|View full text |Cite
|
Sign up to set email alerts
|

Using WhatsApp for Teaching a Course on the Education Profession

Abstract: Social media has gained popularity in the realm of education. However, little research has examined empirically the extent to which students interacting using social media experience a different level of social presence, sense of community and perceived learning compared to those interacting face-to-face. As many as 100 students who were taking a course on Education Profession at the Department of Primary School Teacher Education at Halu Oleo University were recruited for this study. The students were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
2
10
1
3
Order By: Relevance
“…Most students stated that they preferred to use WhatsApp because they were familiar with its features and because it was reasonably affordable when it came to data bundle usage. This finding is similar to other study results (Cetinkaya, 2017;Mulenga & Marbán, 2020;Suardika et al, 2020;Susilo, 2014) that showed WhatsApp as an emerging valuable educational tool in other educational set-ups. This is especially for under-resourced students, who may only have smartphones and low data availability.…”
Section: Students' Involvement In Elearning Before and During The Lockdownsupporting
confidence: 92%
“…Most students stated that they preferred to use WhatsApp because they were familiar with its features and because it was reasonably affordable when it came to data bundle usage. This finding is similar to other study results (Cetinkaya, 2017;Mulenga & Marbán, 2020;Suardika et al, 2020;Susilo, 2014) that showed WhatsApp as an emerging valuable educational tool in other educational set-ups. This is especially for under-resourced students, who may only have smartphones and low data availability.…”
Section: Students' Involvement In Elearning Before and During The Lockdownsupporting
confidence: 92%
“…There are some obstacles to learning, such as the internet access quality at home, the limited interaction between lecturers and students, and the response or feedback. Other studies show the same results that in online learning, the interaction of lecturers and students in various forms is significant [26][27][28].…”
Section: Learning Impactssupporting
confidence: 64%
“…The social media can play an important role in this process and make it possible to organize social interaction. The experience of using social networks to enhance interaction and engagement of students, to encourage peer-support is widely reviewed in the literature - Facebook [ 15 , 16 ], Twitter [ 17 ], blog [ 18 , 19 ], WhatsApp [ 20 , 21 ]. Andersen, and Ponti have analyzed the online nonformal course emphasizing teaching and learning by peers and for peers, where everyone can act as an organizer and as a participant in the course, and vice versa [ 22 ];…”
Section: Literature Reviewmentioning
confidence: 99%